Understanding Anti-COVID-19 Vaccination Protest Slogans in the US - Liao, Tim F. (Frontiers in Communication, 2022)
This study aims to investigate public protest slogans in response to the Biden Administration’s announcement of two COVID-19 vaccination regulations on November 4, 2021. We identified three protest themes: (1) support for individual freedom/rights, (2) opposition to government’s control, and (3) anti-science reasoning/misinformation/disinformation. Major policy recommendations include implementing efforts to dispel unscientific misinformation/disinformation and to emphasize individuals’ civic responsibilities for vaccination during the current COVID-19 pandemic, especially considering the current spreading of the BA.2 variant and the relaxing of mask mandates across the US.